O ensino de funções em escola técnica de nível médio por meio da modelagem matemática e uso da calculadora gráfica - Bilhéo, Luiz Alfredo Dealis (2012)
The difficulty of students in learning concepts of mathematics especially at high schools is current problem in Brazilian schools. This difficulty is a challenge even bigger as the different high school systems are considered, for example, the technical professional high schools. Such challenge for two classrooms of first grade (10th grade in K-12) of a technical course in environmental studies motivated the proposal of this dissertation. The research work explored a teaching methodology of the concept of function that would show to the student the importance of this concept in a technical course, while offering an opportunity to know about the mathematics modeling that uses functions, especially those from school curriculum. The final results of this dissertation consisted of working sheets that were planned, executed and evaluated in two classrooms. The worksheets are formatted so that they can be used by teachers who share the same challenge and interest in developing research to improve the teaching/learning mathematics at high - school level. The proposed activities are based on mathematics modeling of problems in the context of the students course, and on the educational use of a graphic calculator to construct tables, graphs and regression curves. The official documents from Ministry of Education (MEC) about curriculum standards and some theoretical references have been used for our reflections about the differences between traditional teaching style and new educational trends, and about the potential of technology to improve the learning. The work presents also a study of the concept of function that supported the planning of the proposed classroom activities.